Characterization of Androctonus mauritanicus venom and in vitro screening of SARS-CoV-2 entry inhibitors candidates - Chahir, Reda; Galan, Jacob; Hboub, Hicham; Lahlou, Ahmed Salim; Chakir, Salma; Aassila, Hinde; Ben Mrid, Reda; Bouchmaa, Najat; Stöcklin, Reto; El Fatimy, Rachid; Oukkache, Naoual (Frontiers in Pharmacology, 2025)
Animal venom, known for its complex biochemical composition, presents a valuable source of therapeutic molecules, particularly for antiviral applications. Despite this potential, the industrial use of venom remains limited, with fewer than a dozen venom-derived compounds reaching commercial markets. This study underscores the significance of exploring venom’s natural diversity as a reservoir for novel bioactive compounds that could drive innovative drug development. We investigated the venom of the Moroccan black scorpion Androctonus mauritanicus (Am), applying solid-phase extraction (SPE) and high-performance reversed-phase liquid chromatography (RP-HPLC) to fractionate the venom into 80 distinct samples. These fractions were subjected to detailed analysis using advanced mass spectrometry techniques, including ESI-MS, Q-TOF LC/MS, and Q-Exactive LC/MS. In total, 507 unique molecular masses were identified, with several fractions enriched in neurotoxins targeting ion channels (NaScTxs, KScTxs, CaScTxs, and ClScTxs), highlighting their therapeutic relevance. Fractions containing inhibitory molecules targeting the receptor-binding domain (RBD) of the SARS-CoV-2 Spike S protein were identified through in vitro validation via competitive ELISA, showing multiple levels of inhibitory potential. These findings demonstrate the antiviral activity of venom-derived molecules and reveal promising opportunities for venom-based industrial applications targeting SARS-CoV-2. In conclusion, this study not only emphasises the antiviral properties of specific venom molecules but also opens pathways for industrial drug development, offering potential tools to combat emerging viral diseases.